The Pepper Late Embryogenesis Abundant Protein, CaDIL1, Positively Regulates Drought Tolerance and ABA Signaling - Lim, Junsub; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2018)
Plants as sessile organisms constantly respond to environmental stress during their growth and development. The regulation of transpiration via stomata plays crucial roles in plant adaptation to drought stress. Many enzyme-encoding genes are involved in regulation of transpiration via modulating stomatal opening and closure. Here, we demonstrate that Capsicum annuum Drought Induced Late embryogenesis abundant protein 1 (CaDIL1) gene is a critical regulator of transpirational water loss in pepper. The expression of CaDIL1 in pepper leaves was upregulated after exposure to abscisic acid (ABA) and drought. Phenotype analysis showed that CaDIL1-silenced pepper and CaDIL1-overexpressing (OX) Arabidopsis transgenic plants exhibited reduced and enhanced drought tolerance, respectively, accompanied by an altered water loss. Furthermore, ABA sensitivity was significantly lower in CaDIL1-silenced pepper, but higher in CaDIL1-OX plants, than that in control plants, which resulted in opposite responses to drought stress in these two plant types. Collectively, our data suggest that CaDIL1 positively regulates the ABA signaling and drought stress tolerance.